2018
DOI: 10.14336/ad.2017.0415
|View full text |Cite
|
Sign up to set email alerts
|

Brain Interstitial Fluid Drainage Alterations in Glioma-Bearing Rats

Abstract: Real time imaging and measurement of the drug distribution in the brain interstitial space (ISS) are able to determine the effeicency of local brain drug delivery to treatment gliomas. In the present study, we used a tracer-based magnetic resonance imaging (MRI) method to quantitatively analyze the effects of glioma growth on ISF drainage. Sprague-Dawley rats were randomly divided into six groups (n = 6). C6 glioma cells were implanted into either the caudate nucleus or thalamus of rats and then were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We further demonstrated an abnormal leakage of the traced ISF to the adjacent ECS division in a demyelinated rat brain (Fig.4). Indeed, a similar disturbance has been reported in an aggressive C6 glioma model [25]. Thus, we demonstrate that the brain is protected not only by the blood-brain barrier (BBB), which avoids potential exogenous damage through the vascular system, but is also protected by an internal ISF drainage barrier to avoid potentially harmful interference from other ECS divisions in the deep brain.…”
Section: Discussionsupporting
confidence: 82%
“…We further demonstrated an abnormal leakage of the traced ISF to the adjacent ECS division in a demyelinated rat brain (Fig.4). Indeed, a similar disturbance has been reported in an aggressive C6 glioma model [25]. Thus, we demonstrate that the brain is protected not only by the blood-brain barrier (BBB), which avoids potential exogenous damage through the vascular system, but is also protected by an internal ISF drainage barrier to avoid potentially harmful interference from other ECS divisions in the deep brain.…”
Section: Discussionsupporting
confidence: 82%
“…The ECS was thus compartmentalized. In our previous study, we verified that the regionalized ISF drainage is important for maintaining normal brain functions, which can be impeded with cuprizone-induced demyelination [ 5 , 6 , 9 ]. Therefore, we hypothesized that a regionalized ISF drainage provides local homeostasis of the working environment for neurons and glial cells.…”
Section: Discussionmentioning
confidence: 88%
“…Our results suggest that this regionalized ISF drainage system may be of importance for maintaining the brain’s normal function. Combined with previous research, a matured ISF drainage system can prevent transmitters’ interference from different ECS divisions and may assist the remote signal conduction of neurons in the same ECS along the ISF drainage pathway [ 5 , 8 , 9 , 29 ]. Our findings are in keeping with developing literature highlighting a previously underappreciated role of myelin in regulating the ISF drainage [ 8 ], and we show that changes in ISF drainage correlate with the developmental changes in the brain function of rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the technique of direct drug delivery into brain tissues has attracted much attention in recent years [ 32 , 34 , 35 , 36 , 37 , 38 , 39 ]. Han et al reported that injecting drugs into the extracellular space of brain tissues might provide an efficient path to overcome the blood-brain barrier (BBB) in the treatment of stroke [ 40 , 41 , 42 ]. Trans-cranium injection of drugs may also benefit developing novel clinic therapies for brain tumor and other brain function disorders [ 38 , 43 ].…”
Section: Introductionmentioning
confidence: 99%